Reduction of Heavy Metals Level in the Waste Water Using Phytoremediation Technique - Azura Afrina; Lazulva Lazulva (Universitas Negeri Medan, 2018)
This research was carried out due to the existence of the waste heavy metals in the aquatic environment, which was very harmful to the sustainability of the environment. The purpose of this research was to find out the reduction percentage of copper metal (Cu) on the waste. This research using method phytoremediation test. The plants used were water hyacinth (Eichornia crassipes) and algae (Hydrilla verticilata). This study was conducted three times of the repetition in each variable. The measurement of Cu concentration using Atomic Absorption Spectroscopy (AAS) flame. The Results of this research was found that the efficiency of the average reduction in the concentration of Cu by water hyacinth was 82.8368% and the efficiency of the average reduction in the concentration of Cu by algae was 63.4042%.